2017
DOI: 10.3390/ijgi6030078
|View full text |Cite
|
Sign up to set email alerts
|

On Data Quality Assurance and Conflation Entanglement in Crowdsourcing for Environmental Studies

Abstract: Volunteer geographical information (VGI), either in the context of citizen science or the mining of social media, has proven to be useful in various domains including natural hazards, health status, disease epidemics, and biological monitoring. Nonetheless, the variable or unknown data quality due to crowdsourcing settings are still an obstacle for fully integrating these data sources in environmental studies and potentially in policy making. The data curation process, in which a quality assurance (QA) is need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…These annotations, only used when communicating graphically between stakeholders, are conformant to the BPMN standard. The metadata on data quality belongs to three different quality models (see Appendix B for a full description): the producer model, generating the spatial data quality from the ISO19157, the consumer model following the principle of the user feedback model (Geospatial User Feedback Standard Working Group www.opengeospatial.org/projects/groups/gufswg) and the stakeholder quality model [26,36]. The ISO 19157 establishes the principles for describing the quality of geographic data Qualifying each citizen volunteer, the stakeholder quality model produces quality elements that are updated at each new participation in a survey (from running the associated QA) but current values are kept associated with the observation when it is made by this citizen volunteer.…”
Section: Quality Assurance and Quality Control Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…These annotations, only used when communicating graphically between stakeholders, are conformant to the BPMN standard. The metadata on data quality belongs to three different quality models (see Appendix B for a full description): the producer model, generating the spatial data quality from the ISO19157, the consumer model following the principle of the user feedback model (Geospatial User Feedback Standard Working Group www.opengeospatial.org/projects/groups/gufswg) and the stakeholder quality model [26,36]. The ISO 19157 establishes the principles for describing the quality of geographic data Qualifying each citizen volunteer, the stakeholder quality model produces quality elements that are updated at each new participation in a survey (from running the associated QA) but current values are kept associated with the observation when it is made by this citizen volunteer.…”
Section: Quality Assurance and Quality Control Frameworkmentioning
confidence: 99%
“…A screenshot and video of the interface can be viewed in the GitHub repository (https://github.com/cobweb-eu/workflow-at) and shows composition of a QA workflow, including choosing a QC from a list of QCs (classified as one of the 7 pillars), populating the necessary input parameters and input data, then continuing to instantiate the workflow. [26,36].…”
Section: Quality Assurance and Quality Control Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the aforementioned and ongoing research around VGI quality, there is no holistic and comprehensive framework for assessing the overall quality of such data (research in this direction can be found, for example, in [13,14]) and the existing methods (e.g., ISO-based quality evaluation) are not inclusive or flexible enough to accommodate this new type of data.…”
Section: Introductionmentioning
confidence: 99%